Current uses of electro-cautery lumen apposing metal stents in endoscopic ultrasound guided interventions - Yi, Hang; Liu, Qin; He, Song; Zhong, Li; Wu, Su-hua; Guo, Xiao-dong; Ning, Bo (Frontiers in Medicine, 2022)
The electro-cautery lumen apposing metal stent (EC-LAMS) is a newly developed device that integrates the electro-cautery cyctotome with the one-step metal stent delivery and releasing system in recent years. LAMS was first designed to complete the drainage of pancreatic fluid collection under endoscopic ultrasound guidance, and the technological innovation of EC-LAMS has made more off-labeled indications of endoscopic intervention for gastrointestinal diseases realized, such as abdominal fluid drainage, bile duct, or gallbladder drainage through stomach or duodenum, gastrointestinal anastomosis, and the establishment of fistulous channel for further endoscopic operation when necessary. The unique feature of this metal stent is that it has the design of a saddle shape and a large lumen, and can almost connect the adjacent structures to minimize the risk of perforation and leakage. Compared with traditional LAMS, EC-LAMS, an advanced integrated device, can greatly simplify the endoscopic process, shorten the procedure time and reduce the technical difficulty, thus it can help endoscopists complete more complex endoscopic interventions. In this review, we discuss the state of art with regard to EC-LAMS and its endoscopic process, current indications, outcomes, adverse events, and future application prospects.